Sample Survey to Identify Land-Use Pattern of Rice-Based Cropping Systems in Sri Lanka - Madushan, N.D.R.; Herath, H.M.N.M.; Kadupitiya, H.K.; Rathnayake, W.M.U.K.; Dissanayaka, D.M.S.B.; Ariyaratne, M.; Marambe, B.; Sirisena, D.N.; Suriyagoda, L.D.B. (University of Jaffna, 2020)
A survey was conducted to identify land-use pattern of rice-based cropping systems in the country using 9000 samples at the end of the Yala season 2019. Data were gathered by visiting selected paddy fields in a yaya (track) of those sample locations. Data were statistically analysed using the chi-square test in SAS. Out of the lands surveyed, 3.5% of the lands were abandoned. The percentage of abandoned paddy lands were significantly high (p<0.0001) in rain fed areas (7.4%) compared to major (1.4%) and minor (2.5%) irrigation areas. Western province had the highest number of abandoned paddy fields (27%) while it was the lowest in Uva province (0.0%). Out of the total plots surveyed, 67% occupied by paddy and 29% was kept as fallow. Moreover, 1.6%, 1.5%, 0.4% and 0.3% were occupied by other field crops (OFC), vegetables, banana and perennials, respectively. The least % of lands cultivated by paddy (53%) and the highest % of lands kept fallow (43%) was observed in the Northern province. Uva province was dominated by the OFC cultivation (15%) while vegetable was dominated in the Central province (9.4%). Banana was mainly cultivated in the Sabaragamuwa province (5.4%) while 0.9% of paddy lands in Western province were converted to perennial crops. Reasons for diversifying paddy lands to alternative land-uses need to be explored, and the current findings will be useful in making future decisions on rice-based cropping systems to ensure sustainability of those lands
Keywords: Irrigation; Land use-patterns; Rice-based cropping systems